2022
DOI: 10.1155/2022/7927447
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly Synthesis of Carbon Nanoparticles by Laser Ablation in Water and Evaluation of Their Antibacterial Activity

Abstract: Carbon nanomaterials are ground-breaking two-dimensional materials with a wide range of applications because of their unique properties, which include excellent optical, electrical, thermal, and mechanical capabilities; biocompatibility; and inexpensive large-scale production costs. In this study, carbon nanostructural materials (CNMs) were effectively generated using a pulsed laser ablation method on a graphite target immersed in deionized water, and their cytotoxicity and antibacterial activities were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Additionally, several studies have demonstrated that green-synthesized ZnO NPs have demonstrated a high level of wound healing capacity when used as an ointment [ 126 ]. It has been demonstrated that biologically produced ZnO NPs have catalytic properties, enzyme inhibition properties, anti-diabetic efficacy, and anticholinergic properties [ 127 , 128 , 129 , 130 ]. In addition to its blue and near-UV emitting properties, ZnO NPs also emit green or yellow fluorescence characteristics of oxygen vacancies.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Additionally, several studies have demonstrated that green-synthesized ZnO NPs have demonstrated a high level of wound healing capacity when used as an ointment [ 126 ]. It has been demonstrated that biologically produced ZnO NPs have catalytic properties, enzyme inhibition properties, anti-diabetic efficacy, and anticholinergic properties [ 127 , 128 , 129 , 130 ]. In addition to its blue and near-UV emitting properties, ZnO NPs also emit green or yellow fluorescence characteristics of oxygen vacancies.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Figure 2 b displays the results of the XRD structural characterization. The (002) and (100) planes of the GONRs correspond to the two diffraction peaks at 25.0° and 43.0°, respectively 31 . The XRD patterns of the GO/GONRs/SA aerogel are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A graphite pellet with a purity of 99.91% (obtained from National Spectroscopic Electrodes Co.) and a diameter of mm was placed at the bottom of a glass jar filled with 3 mL of deionized water (D-W). The laser energy varied between 60 and 220 mJ, with 75 pulses [59,60]. The production of pristine single-walled carbon nanotubes (SWCNTs) is much sought after due to their extensive use in the sectors of electronics and biomedicine.…”
Section: Laser Ablationmentioning
confidence: 99%